Populism as a keyword and as a meta-discursive resource for positioning in mediated political discourse. (June 2019) - Hamo, Michal; Kampf, Zohar; Weiss-Yaniv, Naama
Abstract: The recent spread of populist ideologies and rhetoric has resulted in growing scholarly attention to the phenomenon, and in 'populism' becoming a salient keyword in contemporary political discourse. However, while there are diversified academic conceptualizations of the term, its vernacular and public uses were hardly studied. The present study aims at addressing this lacuna, by exploring the inductive meanings and functions of 'populism' in Israeli mediated political discourse. To this end, we combined quantitative and qualitative analysis of the reference and linguistic context of a sample of 500 occurrences of 'populism', 'populist' and their inflections in major news outlets during 2012–2017; and detailed discourse analysis of their uses as a meta-discursive resource for positioning in mediated political talk during 2016–2017. Our findings suggest that political actors add a moral-evaluative layer to former conceptualizations of 'populism', and associate it with cynicism and inauthenticity – thus reversing and problematizing populist discourse. We found that 'populism' is a highly flexible and multi-functional positioning resource. It is used in all modes of self-, other-, present and non-present positioning, and strategically employed to challenge antagonists, defend oneself against challenges, manage political images, control the topical agenda of interviews or ensure quotability and news and entertainment values. Such uses reflect the dialogicity and self-reflexivity of contemporary political face management, and tensions between conflicting journalistic normative frameworks and professional practices.